Fee-Paying English Language Learners: Situating International Students’ Impact on British Columbia’s Public Schools - Deschambault, Ryan (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2018)
This article examines the relationship between international education and English as an additional language (EAL) education in British Columbia’s public education system. Drawing on a wide range of data generated as part of a longitudinal study of high school aged fee-paying international students (FISs) in an urban school district in British Columbia, I make the case that FIS recruitment and presence is having a socializing impact on EAL education in British Columbia’s public schools. In contrast to the way FISs are accounted for in official government statistics, I show how, across multiple actors and dimensions of the public system, FISs are routinely treated and represented as English language learners (ELLs). I argue that these routinized constructions are evidence of the multilayered socialization of EAL education by internationalization efforts in British Columbia’s K-12 sector, and discuss some of the ways this FIS socialization is consequential for EAL learning and teaching in public high schools. I situate my discussion of the FIS-EAL relationship within the larger context of applied linguistics and education-related research on internationalization and educational migration in K-12 settings, and raise questions about how FIS socialization is relevant to discussions of public education.